Some properties of g(x)-nil clean graphs of rings - Vivek, Menon Narayanan (2021)
This project aims to study the relationship between ring theory and graph theory, specifically the study of nil-clean graph rings. Rings are those that satisfy the property of being an abelian group under addition and being closed under multiplication. Graphs are structures that consist of a vertex set and an edge set which together, will form various types of connections. Using these concepts, a nil-clean ring